KINERJA PEMBIAYAAN DAN KUALITAS ASET SEBAGAI PENENTU ROA PADA BANK UMUM SYARIAH PERIODE 2020-2024 - Fuji Raodah; Nur Faila; Musdaliva (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the effect of financing performance and asset quality on Return on Assets (ROA) at Islamic Commercial Banks (BUS) in Indonesia during the 2020–2024 period. The COVID-19 pandemic in 2020 led to an increase in non-performing loans (NPF) and a decline in bank profits. However, the economic recovery in 2022–2024 showed improvements in financial indicators. This study uses a descriptive quantitative approach with a panel data regression method for 12 Islamic Commercial Banks registered with the Financial Services Authority (OJK). The variables used include the Financing to Deposit Ratio (FDR) and Non-Performing Financing (NPF) as indicators of financing performance, and Non-Performing Assets (NPF) and Allowance for Impairment Losses (CKPN) as indicators of asset quality. The analysis shows that FDR has a significant positive effect on ROA, while NPF, APB, and CKPN have a significant negative effect on ROA. Simultaneously, all independent variables significantly affect ROA, with a coefficient of determination (R²) of 0.731, meaning that 73.1% of the variation in ROA is explained by financing performance and asset quality. This finding confirms that effective financing intermediation and asset risk management are key factors in maintaining the profitability and stability of Islamic banks in Indonesia during the post-pandemic period